The Danny and the Dinosaur Treasury - Hoff, Syd; Nang ChanYeema (New York, USA HarperCollins Publishers, 1993)
A little boy is surprised and pleased when one of the dinosaurs from the museum agrees to play with him.
Keywords: Story Collection